A comparative study of the academic achievements of the sixth grade graduates and the seventh grade graduates in the University of the Philippines - Hidalgo, Carmen Z. 1916- (1950)
This is a comparative study of the academic achievements of students in the University of the Philippines-- those students who had the six-year elementary education in one group, and those students who had the seven-year elementary education in the other group. General findings say that the Sixth Grade graduates did not show any scholastic inferiority to the Seventh Grade students.